Diabetic nephropathy induces alterations in the glomerular and tubule lipid profiles - Grove, Kerri J; Voziyan, Paul A; Spraggins, Jeffrey M; Wang, Suwan; Paueksakon, Paisit; Harris, Raymond C; Hudson, Billy G; Caprioli, Richard M (Journal of lipid research, 2014)
Diabetic nephropathy (DN) is a major life-threatening complication of diabetes. Renal lesions affect glomeruli and tubules, but the pathogenesis is not completely understood. Phospholipids and glycolipids are molecules that carry out multiple cell functions in health and disease, and their role in DN pathogenesis is unknown. We employed high spatial resolution MALDI imaging MS to determine lipid changes in kidneys of eNOS(-/-) db/db mice, a robust model of DN. Phospholipid and glycolipid structures, localization patterns, and relative tissue levels were determined in individual renal glomeruli and tubules without disturbing tissue morphology. A significant increase in the levels of specific glomerular and tubular lipid species from four different classes, i.e., gangliosides, sulfoglycosphingolipids, lysophospholipids, and phosphatidylethanolamines, was detected in diabetic kidneys compared with nondiabetic controls. Inhibition of nonenzymatic oxidative and glycoxidative pathways attenuated the increase in lipid levels and ameliorated renal pathology, even though blood glucose levels remained unchanged. Our data demonstrate that the levels of specific phospho- and glycolipids in glomeruli and/or tubules are associated with diabetic renal pathology. We suggest that hyperglycemia-induced DN pathogenic mechanisms require intermediate oxidative steps that involve specific phospholipid and glycolipid species.